The Judge's Perception of the Meaning of a Wife Not Being Able to Perform Obligations Under the Requirements of Polygam, a Study in the Amuntai - Kalsum, Umi; Muzainah , Gusti (Fakultas Syariah UIN Antasari, 2024)
This research is motivated by the existence ofArticle 4 paragraph (2)Marriage Law Number 1 of 1974 in conjunction with Law Number 16 of 2019, namely that the wife cannot carry out her obligations as a wife, the wife has a disability or disease athat scannot be cured and the wife cannot give birth to offspring. Regarding the first condition, the law does not explain further or provide clear boundaries regarding what is included in a wife's obligations. Therefore, the judge, as a person who has authority and plays a role in granting or not granting permission for polygamy, can provide or clarify any obligations borne by the wife that cannot be carried out by the wife so that a husband can be given permission to practice polygamy. This research aims to find out the judge's perception in giving the meaning that the wife cannot carry out the obligations stated in the requirements for polygamy and the reasons used by the judge in giving the meaning that the wife cannot carry out the obligations. This research is empirical legal research with a qualitative and descriptive approach. This research was located at the Amuntai Religious Court. Data collection techniques are through observation, interviews and documentation with data sources namely informants from the Amuntai Class 1B Religious Court Judges. Based on the results of research conducted by the author, the meaning of a wife not being able to carry out her obligations under the requirements of polygamy is firstly, the judge in giving the meaning of a wife not being able to carry out her obligations focuses more on the benefit by looking at the facts in the trial, and secondly, the meaning of a wife not being able to carry out her obligations is the inability to carry out her obligations. Inner livelihood is caused by physical, psychological and age factors. The reason used by the judge is that judges cannot be fixated on the law, so that when adjudicating a case they need to pay attention to aspects of justice and benefit, and the next reason is because spiritual support is an absolute obligation of a wife.